Retiring in a Prison Cell: The South African Sentenced Older Adult Male Offender. (March 2023) - Booyens, Karen; Geyer, Stephan; Masenge, Andries
The purpose of this study was to create a profile of the sentenced older adult male offender incarcerated in South African prisons. The findings of this investigation are based on face-to-face surveys with 88 older adult male inmates. In order to develop a comprehensive profile, the study explored offenders' backgrounds, previous and current offenses, lifestyle patterns, physical and mental health, institutional living conditions, release, reintegration, and mortality in prison. These domains are discussed in detail, and recommendations are offered for the treatment and care of this offender group. The recommendations may be applicable to other developing countries in the Global South.